2015
DOI: 10.3945/jn.114.208009
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Iron-Biofortified Pearl Millet in School Children in India ,

Abstract: Fe-PM significantly improved iron status in children by 4 mo compared with Control-PM. This study demonstrated that feeding Fe-PM is an efficacious approach to improve iron status in school-age children and it should be further evaluated for effectiveness in a broader population context. This trial was registered at clinicaltrials.gov as NCT02152150.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(127 citation statements)
references
References 18 publications
(16 reference statements)
5
121
0
1
Order By: Relevance
“…School feeding may help children and adolescents receive sufficient nutrients and grow. The inclusion of micronutrient-rich foods or powders may address anemia and support improved cognition (Abizari and others 2012;Abizari and others 2014;Finkelstein and others 2015). School meals may also foster understanding of healthy diets and behaviors that can extend beyond school and throughout life, particularly if nutrition education is incorporated into the program (Kubik and others 2003;Story, NeumarkSztainer, and French 2002).…”
Section: Nutritionmentioning
confidence: 99%
“…School feeding may help children and adolescents receive sufficient nutrients and grow. The inclusion of micronutrient-rich foods or powders may address anemia and support improved cognition (Abizari and others 2012;Abizari and others 2014;Finkelstein and others 2015). School meals may also foster understanding of healthy diets and behaviors that can extend beyond school and throughout life, particularly if nutrition education is incorporated into the program (Kubik and others 2003;Story, NeumarkSztainer, and French 2002).…”
Section: Nutritionmentioning
confidence: 99%
“…In the studies on iron biofortified crops the biochemical tests that were done to test improvement in the iron status were: Inflammation (measured by C-reactive protein and α-1-acid glycoprotein concentrations) [14,15], total body iron [13][14][15][16][17][18]21,22], haemoglobin concentration [16], serum ferritin concentration [13][14][15][16][17], acute phase proteins [18] and serum transferrin receptor concentration [19]. The baseline cut-offs for each of the parameter differed among the studies (Table 2).…”
Section: Methods Of Nutrient Analysesmentioning
confidence: 99%
“…Studies [13][14][15]17,18] revealed that the subjects' ferritin and total iron increased significantly after feeding intervention with high iron biofortified crops. There was notable increase in the total body iron for subjects who were deficient at the baseline.…”
Section: Effect Of Biofortified Food Crops On Micronutrient Statusmentioning
confidence: 99%
See 2 more Smart Citations